STUDIING MOTIVATION TO SUCCESS DEPENDING ON THE LEVEL OF ENTREPRENEURIAL SKILLS OF EMPLOYEES IN PRODUCTION COLLECTIVES - Yudina, Alina (Psychological Prospects Journal, 2018)
In this article are ascertained the problem of research motivation to success among employees of production collectives. This article presents the study of motivation to success and motivation to avoidance among employees of different collectives of production enterprise. The analysis of psychological factors of motivation to success are described, entrepreneurial skills in particular: needs to achievement in job, needs to autonomy, creative inclinations, the ability to go for a reasonable risk, purposefulness and determination. The article shows study influence of sexual-organizational features on the representation of psychological factors of motivation to success. This paper describes the gender characteristics of managers and workers from production enterprise. The article shows the results of study category of success and category of avoidance among workers from production collectives. Also in this paper are analyzed the significant differences between motivated and unmotivated workers of production collectives by the level of entrepreneurial skills. In article are examined the features of representation worker’s entrepreneurial skills depending on gender and status in organization (position). This work also describes the study of significant differences between managers and workers of production collectives. In this paper are determined and analyzed the significant differences between employees of each sample groups: among managers and among workers by the level of representation entrepreneurial and communicative skills. Besides, in this article are submitted the analysis of relationship between employees’ position, gender and psychological factors of motivation to success. The peculiarities of the influence of position and gender on representation of entrepreneurial, communicative and organizational skills among employees of production collectives was described in this work. This article also presented the study of interaction between employees’ motivation and their entrepreneurial skills. Besides, the study results of interaction between employees’ position, gender and its influence on representation of motivation to avoid failures are analyzed and presented.